Negative pressure therapy (vacuum) for wound bed preparation among diabetic patients: case series - Ferreira, Marcus Castro; Carvalho, Viviane Fernandes de; Kamamoto, Fábio; Tuma Junior, Paulo; Paggiaro, André Oliveira (São Paulo Medical Journal, 2009)
CONTEXT: Complications from diabetes mellitus affecting the lower limbs occur in 40 to 70% of such patients. Neuropathy is the main cause of ulceration and may be associated with vascular impairment. The wound evolves with necrosis and infection, and if not properly treated, amputation may be the end result. Surgical treatment is preferred in complex wounds without spontaneous healing. After debridement of the necrotic tissue, the wound bed needs to be prepared to receive a transplant of either a graft or a flap. Dressings can be used to prepare the wound bed, but this usually leads to longer duration of hospitalization. Negative pressure using a vacuum system has been proposed for speeding up the treatment. This paper had the objective of analyzing the effects of this therapy on wound bed preparation among diabetic patients. CASE SERIES: Eighty-four diabetic patients with wounds in their lower limbs were studied. A commercially available vacuum system was used for all patients after adequate debridement of necrotic tissues. For 65 patients, skin grafts completed the treatment and for the other 19, skin flaps were used. Wound bed preparation was achieved over an average time of 7.51 days for 65 patients and 10 days for 12 patients, and in only one case was not achieved. CONCLUSIONS: This experience suggests that negative pressure therapy may have an important role in wound bed preparation and as part of the treatment for wounds in the lower limbs of diabetic patients.